Enhanced hydrogen production by optimization of immobilized cells of the green alga Tetraspora sp. CU2551 grown under anaerobic condition - Maswanna, Thanaporn; Phunpruch, Saranya; Lindblad, Peter; Maneeruttanarungroj, Cherdsak (My University, 2018)
The green alga Tetraspora sp. CU2551 has previously been identified and characterized as a photosynthetic microorganism with high potential for H2 production. In the present study, cells of Tetraspora CU2551 were entrapped and immobilized in an alginate matrix with the aim to analyze the effect of cell stacking and a reduced exposure of O2 to the cells. The results showed that the most favorable immobilization conditions were 4% (w/v) of final alginate concentration and a cell concentration of 0.125 mg cell dry wt/mL alginate with a bead diameter of 2.80–3.35 mm. The H2 production yields increased when the immobilized cells were incubated in S-deprived medium and this could be repeated at least for 3 production times. Maximal total H2 production reached 7.68 ± 0.88 mL H2/25 mL medium, corresponding to a rate of 1182.45 ± 24.40 nmol H2/h/mg DW. This production is about 6 times higher compared to by cells in suspension, 2–10 times higher when compared to by other green algae, and 10–50 times higher when comparing with cyanobacteria. Based on our observations, immobilized cells of Tetraspora CU2551 is considered a very promising biological system for significant photobiological H2 production by a photosynthetic microorganism.
Keywords: Alginate; Biohydrogen production; Green algae; Immobilization; Tetraspora sp. CU2551